Role of handloom board to generate employment in rural area: a study of Enaitpur Thana in Sirajgonj - Khan, Md. Ashraful Momin (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.